Surgical management of urolithiasis : percutaneous, shockwave and ureteroscopy - Pearle, Margaret S.; Nakada, Stephen Y. (Springer New York, 2013)
Written entirely by surgical urologists, Surgical Management of Urolithiasis: Percutaneous, Shockwave and Ureteroscopy presents a comprehensive overview of the past, present, and future of surgical techniques, with a focus on educating urologists on the full spectrum of stone procedures.  In addition to the technical issues, detailed complications are described. Basic as well as advanced techniques are presented in both a didactic and visual mode with representative endoscopic images and radiographs. Recent advancements which are not routinely a core component of surgical training programs are also covered in detail. Compact and extensively illustrated, Surgical Management of Urolithiasis: Percutaneous, Shockwave and Ureteroscopy is a unique and valuable resource in the field of surgical urolithiasis, essential both for those currently in training and for those already in clinical practice.